Russian-Japanese bilateral relations: limits of rapprochement - Nelidov V.V. (Восточная Азия: факты и аналитика, 2019)
The article evaluates the current state of Russian-Japanese relations and analyzes the reasons why, despite the active top-level political dialogue, which particularly intensified since 2016, the two nations failed to achieve substantial progress in concluding the peace treaty. The author notes that, besides the incompatibility of the countries‟ positions regarding the issue of territorial delimitation, these reasons also include the difference in their approaches regarding key international political issues, low degree of economic interdependence, as well as several subjective and domestic political factors.